Investigating academic achievement of English medium instruction courses in Turkey - Altay, Mehmet; Curle, Samantha; Yuksel, Dogan; Soruç, Adem (Studies in Second Language Learning and Teaching, 2022)
This article reports a quantitative study that investigated academic achievement in English medium instruction (EMI) courses at a public university in Turkey. Student test score data on EMI and Turkish medium instruction (TMI) courses as well as general English proficiency scores were collected in two academic divisions: the mathematical, physical, and life sciences (MPLS, N = 357); and the social sciences (N = 359). Analysis conducted at the macro (academic division), meso (academic department), and micro levels (academic program) showed subtle differences at each level. Overall, results were consistent: English language proficiency was a strong predictor of academic achievement of social science participants, whereas success in TMI courses predicted EMI success of MPLS participants. These results reinforce the notion that more language support should be given to social science students, whereas learning some content through TMI should be prioritized for MPLS students. Implications for language professionals and EMI practitioners are discussed, and suggestions are made for further research.